Generation and preclinical characterization of an antibody specific for SEMA4D. Issue 1 (2nd January 2016) - Fisher, Terrence L.; Reilly, Christine A.; Winter, Laurie A.; Pandina, Tracy; Jonason, Alan; Scrivens, Maria; Balch, Leslie; Bussler, Holm; Torno, Sebold; Seils, Jennifer; Mueller, Loretta; Huang, He; et al.
Abstract : Semaphorin 4D (SEMA4D or CD100) is a member of the semaphorin family of proteins and an important mediator of the movement and differentiation of multiple cell types, including those of the immune, vascular, and nervous systems. Blocking the binding of SEMA4D to its receptors can result in physiologic changes that may have implications in cancer, autoimmune, and neurological disease. To study the effects of blocking SEMA4D, we generated, in SEMA4D-deficient mice, a panel of SEMA4D-specific hybridomas that react with murine, primate, and human SEMA4D. Utilizing the complementarity-determining regions from one of these hybridomas (mAb 67-2), we generated VX15/2503, a humanized IgG4 monoclonal antibody that is currently in clinical development for the potential treatment of various malignancies and neurodegenerative disorders, including multiple sclerosis and Huntington's disease. This work describes the generation and characterization of VX15/2503, including in vitro functional testing, epitope mapping, and an in vivo demonstration of efficacy in an animal model of rheumatoid arthritis.